Fungsi Manajemen Kepala Ruangan terhadap Kelengkapan Pendokumentasian Perawat - Mukhtar, Nur Azizah Wahdah; Samsualam; Amir, Haeril; Andi Mappanganro (Window of Nursing Journal, 2024)
Nursing services have an important role in improving the quality of health services. Increased public awareness of the quality of quality nursing services is an important factor in the development of hospitals. Improving the quality of nursing care services is closely related to the implementation of the management function of the head of the room as illustrated by the documentation of nursing care. This study aims to determine the effect of the management function of the head of the room on the completeness of documentation for nurses in Labuang Baji Hospital, South Sulawesi Province. The research design used in this study is a descriptive design with a cross sectional approach. The sample provisions were carried out by total sampling technique with a sample of 45 respondents in the Baji Dakka, Baji Ampe, and Baji Nyawa. The data analysis used in this study was the statistical analysis of the T-test. The results showed that there was an influence between the management function of the head of the room on the completeness of the documentation of nurses in the inpatient room at Labuang Baji Hospital, South Sulawesi Province (p-value 0,001) <0,05. The conclusion of this study is that there is an influence between the management function of the head of the room on the completeness of the documentation of nurses in the inpatient room at Labuang Baji Hospital, South Sulawesi Province. It is expected to improve the management function of the head of the room by attending training or seminars on work productivity and evaluating the completeness of nursing documentation on a regular basis.